Impact of service quality on female users trust and loyalty : a study on telecenter as information service providers in Malaysia - Mohd Ridwan Seman @ Kamarulzaman (Kulliyyah of Information, Communication & Technology, International Islamic University Malaysia, 2016)
For the past few years, government of Malaysia and several scholars have paid a substantial amount of attention towards the acceptance, impact and sustainability of telecenter. Although enormous research efforts have been put forth, telecenter are still not fully utilized and not fully populated by the targeted community. The community realizes and aware of the benefit of using Telecenter but what is next. The question about the service quality offered by telecenter, retention of the users after using the services and their satisfaction toward the service quality of telecenter remain unanswered. As far as the researcher concern, there is no researches have been done on service quality that are being offered by telecenter particularly with female users of telecenter. Thus, this study aims to provide a better understanding on service quality relationship with the loyalty and trust of female users of telecenter and the mediating effect of satisfaction and commitment between service quality, trust and loyalty. A research model is developed to identify and evaluate the key driving factors influencing trust and loyalty of the female users of telecenter. The research model is grounded in Gap Model @ SERVQUAL model and is adapted to explain the mediating effects of satisfaction and commitment. A questionnaires survey technique is employed to collect data from female user of telecenter who have experiences in using telecenter and sometime a regular customer of telecenter. Three hundred ten (310) useable responses were received and further analysed using the appropriate statistical procedures. The research model was then tested using the Partial Least Square (PLS) technique. Smart PLS 3.0 was used to validate the research model and test the proposed research hypotheses.This study confirms that service quality (such as tangible, responsiveness, reliability, assurance and empathy) drive female user's loyalty and trust. The empirical results of this study lead to several significant findings. The findings show that service quality positively influences loyalty and trust of female users. Further, satisfaction and commitment have positive significant mediation effect on loyalty and trust of female users of telecenter. These two constructs (i.e., satisfaction and commitment) have been identified to have varied mediation effects (mostly partially). Overall, the research model explains a substantial amount of variance (50%) in trust and (54%) in loyalty.Given the substantial explanatory power of the model findings, this thesis has significant theoretical and practical contributions. Theoretically, this study provides a theoretical model that explains the determinants of loyalty and trust within female users of telecenter context. The theoretical contributions lie in extending the current Gap model @ SERVQUAL theoretical framework. Two constructs (i.e., satisfaction and commitment) are demonstrated to mediate significantly the relationship between loyalty and trust of female users of telecenter with service quality (tangible, assurance, responsiveness, reliability and empathy). Further, this study also provides understanding and practical suggestions on how these determinants influence the loyalty and trust of female telecenter users.